Prevalence and factors associated with severe depressive symptoms in older west African people living with HIV - (:unkn) unknown (My University, 2020)
BackgroundDepression is one of the most common psychiatric disorders in people living with HIV (PLHIV). Depression has a negative impact on both mental and physical health and is mainly associated with suboptimal HIV treatment outcomes. To encourage successful aging and the achievement of the 3 × 90 objectives in older PLHIV, the psychological domain must not be neglected. In this context and as data are scarce in West Africa, this study aimed to evaluate the prevalence and the factors associated with severe depressive symptoms in older PLHIV living in this region of the world.MethodsData from PLHIV aged ≥50 years and on ART since ≥6 months were collected in three clinics (two in Côte d’Ivoire, one in Senegal) participating in the West Africa International epidemiological Databases to Evaluate AIDS (IeDEA) collaboration. The severity of depressive symptoms was measured using the Center for Epidemiological Studies Depression scale (CES-D), and associated factors were identified using logistic regressions.ResultsThe median age of the 334 PLHIV included in the study was 56.7 (53.5–61.1), 57.8% were female, and 87.1% had an undetectable viral load. The prevalence of severe depressive symptoms was 17.9% [95% Confidence Interval (95% CI): 13.8–22.0]. PLHIV with severe depressive symptoms were more likely to be unemployed (adjusted Odd Ratio (aOR) = 2.8; 95% CI: 1.4–5.7), and to be current or former tobacco smokers (aOR = 2.6; 95% CI: 1.3–5.4) but were less likely to be overweight or obese (aOR = 0.4; 95% CI: 0.2–0.8).ConclusionsThe prevalence of severe depressive symptoms is high among older PLHIV living in West Africa. Unemployed PLHIV and tobacco smokers should be seen as vulnerable and in need of additional support. Further studies are needed to describe in more details the reality of the aging experience for PLHIV living in SSA. The integration of screening and management of depression in the standard of care of PLHI
Keywords: African Research